2017
DOI: 10.1186/s12879-016-2162-2
|View full text |Cite
|
Sign up to set email alerts
|

Depression, alcohol use, and intimate partner violence among outpatients in rural Uganda: vulnerabilities for HIV, STIs and high risk sexual behavior

Abstract: BackgroundIntimate partner violence (IPV), alcohol use, and depression are key vulnerabilities for HIV in Uganda, and taken together may have a synergistic effect on risk. Our objective was to investigate the associations between depression, IPV, and alcohol use and HIV-risk indicators among a sample of outpatients in rural Uganda, and the effect of co-occurrence of these factors on HIV-risk indicators.MethodsIn a structured interview we collected data on high-risk sexual behavior, depression symptoms, emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 60 publications
(57 reference statements)
6
39
2
Order By: Relevance
“…Our findings related to depression are consistent with other research in sub-Saharan Africa [31, 32]; more depression may signify less self-care or less hope about the future. Protective factors were condom use self-efficacy and drinking-and-protected-sex days.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings related to depression are consistent with other research in sub-Saharan Africa [31, 32]; more depression may signify less self-care or less hope about the future. Protective factors were condom use self-efficacy and drinking-and-protected-sex days.…”
Section: Discussionsupporting
confidence: 92%
“…In a study of outpatients in rural Uganda, Kiene and colleagues examined the associations between depression, partner violence, and alcohol use and HIV-risk indicators. They found that depression was associated with sexual risk behaviors for men and women and with HIV infection and STI for women [31]. In a study of 738 patrons of alcohol establishments in South Africa, Sikkema and colleagues found that unprotected sex was associated with depression, anxiety and alcohol use among women [32].…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent with the apparent increase in substance use in SSA, human immunodeficiency virus (HIV) remains a major public health problem, with young women aged 15-24 years and people who inject drugs disproportionately affected [7]. In a recent systematic review, we showed that in SSA, information on the burden of alcohol misuse and illicit drug use is limited, especially among young people belonging to certain occupational groups (i.e., sex workers, miners, truckers, fishing communities, uniformed personnel and motorcycle taxi riders) known to be at increased risk of HIV acquisition [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…HIV prevalence in Uganda is among the highest in the world, with national prevalence estimated at 6.2% [1] and prevalence among high risk populations such as fisherfolk and female sex workers at 30% [2] and 33% [3] respectively. While Uganda has been the site of abundant HIV prevention and research efforts, it is one of only two countries in Sub-Saharan Africa (SSA) in which HIV incidence is increasing, particularly in the general population [4]. There is some indication that unaddressed factors including injection and non-injection drug use may be impairing Uganda's HIV prevention efforts [5,6].…”
Section: Introductionmentioning
confidence: 99%